2021
DOI: 10.1158/1940-6207.capr-20-0220
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Cholecystokinin Receptor: A Novel Approach for Treatment and Prevention of Hepatocellular Cancer

Abstract: Hepatocellular carcinoma (HCC) is the fastest growing cancer worldwide in part due to the obesity epidemic and fatty liver disease, particularly nonalcoholic steatohepatitis (NASH). Chronic inflammation with the release of cytokines and chemokines with activation of hepatic stellate cells results in changes of the liver extracellular matrix (ECM) that predisposes to the development of HCC. Blood levels of the gastrointestinal peptide cholecystokinin (CCK) are increased in humans and mice consuming a high-fat d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…We have previously shown that proglumide therapy could decrease fibrosis by preventing stellate cell activation in the mouse liver [21] and in the pancreas microenvironment [61]; therefore, we assume that the anti-fibrotic effect seen in the livers of the CDE-fed mice treated with proglumide in this investigation was related to the blockade of the CCK receptor on mouse stellate cells in the liver. The reduction in hepatic inflammation observed in the CDE/Prog-treated mice of this study may be due to proglumide's action on reducing inflammatory cytokines and chemokines as previously described [27]. The mechanism by which proglumide decreases cytokines and inflammation is unknown; however, CCK receptors and chemokine receptors are both G-protein coupled receptors (GPCRs).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We have previously shown that proglumide therapy could decrease fibrosis by preventing stellate cell activation in the mouse liver [21] and in the pancreas microenvironment [61]; therefore, we assume that the anti-fibrotic effect seen in the livers of the CDE-fed mice treated with proglumide in this investigation was related to the blockade of the CCK receptor on mouse stellate cells in the liver. The reduction in hepatic inflammation observed in the CDE/Prog-treated mice of this study may be due to proglumide's action on reducing inflammatory cytokines and chemokines as previously described [27]. The mechanism by which proglumide decreases cytokines and inflammation is unknown; however, CCK receptors and chemokine receptors are both G-protein coupled receptors (GPCRs).…”
Section: Discussionsupporting
confidence: 76%
“…This study showed that a cholecystokinin receptor inhibitor, proglumide, decreases the histologic and biochemical development of NASH in a murine model. One mechanism of action to explain this finding was previously attributed to the interaction of proglumide at the CCK-B receptors that are increased in expression in the mouse NASH liver [27]. However, a novel finding of this investigation is that proglumide also decreases NASH by acting as a partial agonist at the farnesoid X receptor in the murine liver.…”
Section: Discussionmentioning
confidence: 71%
“…Serum levels of CCK are elevated in HCC patients, and CCK blockade is a novel approach for the prevention/treatment of HCC. ( Tucker et al, 2020 ; Gay et al, 2021 ). However, there are few studies on the relationship between TACR1 and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The cholecystokinin-B receptor (CCK-BR) is not found in normal liver tissue (mouse or human) but becomes overexpressed in NASH and HCC [ 18 ]. In fact, in [ 19 ] 35% of the mice on a NASH-inducing diet developed dysplastic nodules or HCC after 18 weeks, while none of the mice treated with a CCK-BR antagonist, proglumide, developed HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in [ 19 ] 35% of the mice on a NASH-inducing diet developed dysplastic nodules or HCC after 18 weeks, while none of the mice treated with a CCK-BR antagonist, proglumide, developed HCC. Further examination of the mouse NASH livers in this study showed that treatment with the CCK receptor antagonist, proglumide, rendered the liver microenvironment less carcinogenic by decreasing fibrosis, inflammatory chemokines, and cytokines and reducing M2-polarized macrophages [ 18 ]. In fact, treatment of mice bearing HCC tumors with proglumide monotherapy resulted in a significant reduction in cancer growth compared with controls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%